2019
DOI: 10.1177/1756284819851677
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and endoscopic features of severe acute gastrointestinal bleeding in elderly patients treated with direct oral anticoagulants: a multicentre study

Abstract: Background: The aim of the study was to describe the clinical and endoscopic characteristics and management of severe acute gastrointestinal (GI) bleeding in patients treated with direct oral anticoagulants (DOACs). Methods: Patients hospitalized for severe GI bleeding under DOAC therapy were identified in 36 centres between June 2013 and March 2016. Clinical outcomes including re-bleeding, major cerebral and cardiovascular events or all-cause mortality were assessed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…The main outcome of this study was the occurrence of complications that could lead to surgery, including severe GI bleeding, stenosis, and perforations. Severe GI bleeding was defined as hemorrhage in any part of the digestive tract with a Glasgow-Blatchford score ≥6 8 , 9 confirmed by endoscopy, CT scan, and/or interventional radiology. We considered the cause for bleeding to be exclusively associated with CD.…”
Section: Methodsmentioning
confidence: 99%
“…The main outcome of this study was the occurrence of complications that could lead to surgery, including severe GI bleeding, stenosis, and perforations. Severe GI bleeding was defined as hemorrhage in any part of the digestive tract with a Glasgow-Blatchford score ≥6 8 , 9 confirmed by endoscopy, CT scan, and/or interventional radiology. We considered the cause for bleeding to be exclusively associated with CD.…”
Section: Methodsmentioning
confidence: 99%
“…They have reported that half of the cause of mortality was GI bleeding. ( 32 ) In contrast, Brodie et al ( 33 ) have also reported that no death occurred at day 30 in an American retrospective cohort. We have first to report clinical outcomes including mortality and required units of blood transfusions in DOAC-treated or warfarin-treated extremely elderly patients with diverticular bleeding.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, in our data there was not significant differences in mortality between DOAC-treated and warfarin-treated extremely elderly patients in spite of high ratios of discontinuation of oral anticoagulant therapy in both groups. Deutsch et al ( 32 ) have reported mortality rate at the day 30 was relatively high (11.8%) in elderly patients treated with DOACs. They have reported that half of the cause of mortality was GI bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…In OAC reversal studies and observational cohorts, 30-day all-cause mortality after OAC-associated major GI bleeding is 11%-13%. 6,7,17,41,52 For example, in the RE-VERSE AD and ANNEXA-4 studies, all-cause mortality among patients presenting with acute major GI bleeding was 11% and 13%, respectively, despite the treatment with agents that reversed anticoagulant effect and reduced levels of active drug. 6 Subgroup analyses of the ROCKET AF and ENGAGE TIMI trials reported case-fatality rates (adjudicated as death due to bleeding) of 1.7% and 2.1% among patients receiving rivaroxaban or edoxaban, respectively.…”
Section: Mortalitymentioning
confidence: 99%